ChemInform Abstract: Crotocascarins I—K (I), (II): Crotofolane‐Type Diterpenoids, Crotocascarin γ (III), Isocrotofolane Glucoside (IV) and Phenolic Glycoside (V) from the Leaves of Croton cascarilloides. Issue 16 (March 2016) - Kawakami, Susumu; Matsunami, Katsuyoshi; Otsuka, Hideaki; Inagaki, Masanori; Takeda, Yoshio; Kawahata, Masatoshi; Yamaguchi, Kentaro
Abstract: isolation and structure elucidation